Rola wsparcia społecznego w leczeniu cukrzycy u młodzieży - Strzelczyk, Dorota; Szymańska, Sylwia (Acta Universitatis Lodziensis. Folia Psychologica, 2011)
The article is a report of studies on the relationship between social support and the effectiveness of treatment for diabetes in youth. The aim of this study was to answer the question whether between patients with different treatment outcome differences in perceived social support. The study were 100-strong group of diabetics aged 16–18 years (50 girls and 50 boys), which has been assigned to groups of varying effectiveness of diabetes management. Adopted two criteria for allocation of subjects into groups: 1) the level of self-control of diabetes measured by the scale of „Treatment of Diabetes”(LC), 2) the degree of metabolic control measured by HbA1c. To measure the social support Sarason’s Social Support Questionnaire was used. Analysis of test results does not reveal significant differences in social support among patients with high and low self-control. In patients with varying degrees of metabolic control of diabetes patients with poor treatment outcome perceive less social support network (p < 0.05), but they are more satisfied with it (p < 0.01) than patients with good control of diabetes. In addition, the length of morbidity of diabetes is moderately, negatively correlated with the network of support and the degree of satisfaction with the aid received.